2006
DOI: 10.2214/ajr.05.0386
|View full text |Cite
|
Sign up to set email alerts
|

MRI in Evaluating Atrophy of the External Anal Sphincter in Patients with Fecal Incontinence

Abstract: External phased-array MRI is comparable to endoanal MRI in depicting external anal sphincter atrophy and, thereby, in selecting patients for anal sphincter repair. Because results among interpreters varied considerably depending on the experience level, both techniques can be recommended in the diagnostic workup of fecal incontinence only if sufficient experience is available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
40
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 41 publications
(77 reference statements)
4
40
0
1
Order By: Relevance
“…Intraobserver correlation of pelvic organ prolapse has been weak even in single-site studies (12). Moderate and moderate-to-good interobserver correlation of external anal sphincter atrophy on endoanal ( ϭ 0.53-0.56) and phased-array coil ( ϭ 0.55-0.80) MR imaging have been reported (15). Better interobserver correlation has been shown in other singlecenter studies (10,11).…”
mentioning
confidence: 96%
“…Intraobserver correlation of pelvic organ prolapse has been weak even in single-site studies (12). Moderate and moderate-to-good interobserver correlation of external anal sphincter atrophy on endoanal ( ϭ 0.53-0.56) and phased-array coil ( ϭ 0.55-0.80) MR imaging have been reported (15). Better interobserver correlation has been shown in other singlecenter studies (10,11).…”
mentioning
confidence: 96%
“…Two recent studies in 30 patients with faecal incontinence have shown that this technique, despite its inferior local spatial resolution, is comparable with endoanal MR imaging for the depiction of anal sphincter defects and EAS atrophy (Fig. 8) [68,69]. The interobserver agreement for assessing anal sphincter integrity is moderate for endoanal MR imaging and poor to fair for external phased array MR imaging [69,70].…”
Section: Mr Imagingmentioning
confidence: 93%
“…The intraobserver agreement for detecting anal sphincter defects ranged from fair to very good for endoanal MR imaging and external phased array MR imaging [69]. Only one study evaluated the observer reproducibility in assessing EAS atrophy with MR imaging and reported that the interobserver agreement was moderate for endoanal MR imaging and moderate to good for external phased array MR imaging [68]. The intraobserver agreement for detecting EAS atrophy was moderate to very good for endoanal MR imaging and fair to very good for external phased array MR imaging.…”
Section: Mr Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, it is understandable that sphincteroplasty has a place because of its ease of performance, its sustainable improvement in functional outcome (at least for a foreseeable 3-5 years) and its repeatability [14]. The first-line management of the known sphincter defect with SNS will have implications regarding the accuracy of external anal sphincter defect and atrophy imaging definition [15] and should see a reduction in the national number of sphincteroplasties over time [16]. This approach is also reflected in the disappearance of dynamic graciloplasty and the ABS-Acticon device as alternatives have become available and where the side-effects and reoperations required for device complications, infection and extrusion have proven unacceptable both to the specialists performing the surgery and to the patient market force.…”
Section: Introductionmentioning
confidence: 99%